Pajanan CO dan PM10 pada Petugas Bengkel Mobil: Analisis Risiko Kesehatan Lingkungan - Auliya, Vena Nur; Wicaksono, Rizky Rahadian; Syakbanah, Nur Lathifah; Aniriani, Gading Wilda (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The workshop is a work environment with elevated levels of carbon monoxide (CO) and particulate matter (PM10) hazards. The objective of this research is to analyze the environmental health risks due to exposure to carbon monoxide (CO) and particulate matter 10 (PM10) at Putra Mandiri Lamongan Car Workshop. The present research employed an analytical observational design, utilizing the Environmental Health Risk Analysis (ARKL) method for a cohort of six mechanical workers. The collection of data was executed through the measurement of air samples using a carbon monoxide (CO) meter, a particle counter, and a questionnaire. The findings indicate that the CO concentration at points 1 and 3 surpasses the quality standards stipulated in PP Number 22 of 2021, with levels of 14.89 mg/m3 and 17.75 mg/m3, respectively. Additionally, the PM10 concentration at point 1 exceeds the quality standard of 0.08 mg/m3. The real-time RQ values for CO and PM10 at three measurement points remain within the safe range (RQ<1), with the exception of a respondent who is not safe from CO exposure at point 3, having (RQ=1.1439). Subsequently, a reduction in the permissible CO exposure concentration at point 3 to 15.517 mg/m3 is imperative. The risk characterization value of exposure to CO and particulate matter (PM10) for Putra Mandiri Lamongan mechanical workers was categorized as safe (RQ<1), with the exception of one respondent. The management of risk is achieved through the implementation of methodologies aimed at the reduction of CO exposure to safe concentrations, phytoremediation, and the requisite utilization of masks.